OPTIMALISASI PENGELOLAAN WAKAF PRODUKTIF MELALUI PELATIHAN MANAJEMEN WAKAF BAGI NAZHIR MASJID ALAUDDIN DI DESA LAMIDUR - Hakim Siregar, Lukman; Antoro, Budi; Taib, Zulkifli; Reza Septriawan, Muhammad (ABDI DALEM: Jurnal Pengabdian Kepada Masyarakat, 2024)
Abstract This community service activity aims to enhance the capacity of the Badan Kemakmuran Masjid (BKM) administrators in managing productive waqf in Lamidur Village, Simalungun Regency. The training was conducted on September 16, 2024, using a participatory approach that included socialization, counseling, and hands-on practice. Evaluation results indicated that participants experienced a significant increase in understanding of waqf concepts and management, with a satisfaction rate of 90%. Participants demonstrated enthusiasm during the Q&A sessions and successfully developed realistic management plans for waqf assets oriented toward local economic empowerment. This activity is expected to improve community welfare through more effective waqf management. Follow-up monitoring will be conducted to ensure the application of knowledge gained in waqf management in the future.